Care coordination in two of Bogota’s public healthcare networks: A cross-sectional study among doctors (2019)
Introduction: Care coordination is a priority concern for healthcare systems. In Colombia, there is a lack of information on the topic. This study analysed how doctors of two Bogotá’s public healthcare networks perceived coordination between healthcare levels and what factors are associated with their perception. Methods: A cross-sectional study using the COORDENA-CO questionnaire to a sample of 363 doctors (network-1 = 181; network-2 = 182) in 2015. The questionnaire asks about types and dimensions of care coordination: information and clinical management, with items in a Likert scale, as well as conditions regarding health system, organisational and doctors’ conditions. Descriptive statistics and logistic regression analysis were performed. Results: The doctors’ perception of a high level of coordination did not exceed 25.4%. On coordination of information, limited transfer of clinical information was found. Concerning clinical management, there were limited care coherence, deficits in patient follow-up and lengthy waiting times for specialised care. A high perception of coordination were associated with being female, being over 50 years old, being a specialist, having less than one year’s working experience, working less than 20 h per week at the centre, forming part of network-1, having time available for performing coordination tasks, having job satisfaction and not identifying limitations imposed by healthcare insurers. Discussion: There was limited perception of coordination, in its different dimensions and types with some differences between networks. The results support the importance of guaranteeing job satisfaction, ensuring sufficient time to coordination-related activities and intervening in the restrictions imposed by healthcare insurers to improve care coordination. © The Author(s) 2019.